If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 7) + -1(2x + -3) = 3 Reorder the terms: 5(7 + x) + -1(2x + -3) = 3 (7 * 5 + x * 5) + -1(2x + -3) = 3 (35 + 5x) + -1(2x + -3) = 3 Reorder the terms: 35 + 5x + -1(-3 + 2x) = 3 35 + 5x + (-3 * -1 + 2x * -1) = 3 35 + 5x + (3 + -2x) = 3 Reorder the terms: 35 + 3 + 5x + -2x = 3 Combine like terms: 35 + 3 = 38 38 + 5x + -2x = 3 Combine like terms: 5x + -2x = 3x 38 + 3x = 3 Solving 38 + 3x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 3x = 3 + -38 Combine like terms: 38 + -38 = 0 0 + 3x = 3 + -38 3x = 3 + -38 Combine like terms: 3 + -38 = -35 3x = -35 Divide each side by '3'. x = -11.66666667 Simplifying x = -11.66666667
| x^3-x=0.2 | | 3/2a=18 | | x/5/3=1/2 | | 11=-7x-3 | | 4y^2-48y-1152=0 | | -5+2=3 | | 7x+5y=-24 | | 2x+4+x= | | 112-(5x+12)=5(x-9)+x | | 2/t-1=3 | | 30.00/3.00-5(3.50) | | X-8/9=4/9 | | 8x-108=8 | | 17x+35=4+5x-5 | | 8/3=1/2x=-13(6) | | 3(a+b)=3a+3b | | C-5/6=4/9 | | 3(2x+5)=4x+2 | | 0.5x-0.3(40+x)=0.4(60) | | cos(x)=(1/2) | | Y+9.04=6 | | 0.6x-0.5(3)=0.3 | | 7x+53=12+x+2 | | f(x)=-5-7x | | -x-2y=-14 | | 19/3=m/16 | | 11-9(n+3)=20 | | 6(14-2y)+3y=20 | | 7x+74=10x+5 | | -27=9x/7 | | x=8.1-8.9 | | -4y=-6x+20 |